The Effect of Consumption of Red Ginger Extract on the Pain Scale Intensity of Perineal Laceration Wounds in Postpartum Mothers in the Working Area of Jalancagak Health Center, Subang Regency, Indonesia - Eli Sapitri Fikriyani (HM Publisher, 2023)
Red ginger can be used as a natural ingredient in making potions used to treat perineal wounds. This study aimed to determine the effect of the consumption of red ginger extract on the intensity of the pain scale for perineal laceration wounds in postpartum mothers in the working area of Jalancagak Health Center, Subang Regency, Indonesia. This study is a quasi-experimental design with a pretest and post-test with a control group research design. This study used two groups, namely a control group and an intervention group. The pain scale was measured before (pretest) in the intervention and control groups and after (posttest) in the control and intervention groups. The intervention group was given red ginger extract and still received standard management procedures in the form of analgesics, while the control group was only given standard management procedures. A total of 30 research subjects took part in this study and were grouped into a control group and an intervention group. Administration of red ginger extract showed the potential to reduce pain intensity statistically significantly, p<0.05. Similar results were also shown in the control group, where placebo administration was able to reduce pain intensity statistically significantly, p<0.05. The reduction in pain intensity was more optimal in the treatment group compared to the control group, p<0.05. In conclusion, there is an effect of the consumption of red ginger extract on the intensity of the pain scale for perineal laceration wounds in postpartum mothers in the working area of Jalancagak Health Center, Subang Regency, Indonesia.